Determinants of Nurses Performance at H. Padjonga Dg. Ngalle Hospital in Takalar Regency – A Cross Sectional Study - Syukma Ekawati; Indar; Balqis Nazaruddin; Muhammad Alwy Arifin; Aminuddin Syam; Stang; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Nursing services in hospitals are a critical component, requiring reliable nurses with strong motivation to perform their duties, which include providing nursing care. The higher the desired demands, the heavier the burden felt by nurses in providing safe and effective care. Therefore, evaluating nurse performance is essential and should always be carried out through a standardized system to ensure more objective results and evaluations. This study to identify the determinants of nurses performance at H. Padjonga Dg. Ngalle hospital. This is a quantitative research study with a cross-sectional approach. The sample consists of 149 professional nurses. Data were collected using questionnaires and analyzed using chi-square and logistic regression tests. The study results indicate that workload affects nurse performance with a p-value of 0.000 < 0.05, shift work affects nurse performance with a p-value of 0.005 < 0.05 and dual roles affect nurse performance with a p-value of 0.000 < 0.05. Multivariate analysis indicates that the primary factor affecting nurse performance is workload. Hospitals are encouraged to ensure that all nurses maintain a balanced workload to sustain nurse productivity.